2006
DOI: 10.1186/1471-2407-6-256
|View full text |Cite
|
Sign up to set email alerts
|

High Smac/DIABLO expression is associated with early local recurrence of cervical cancer

Abstract: BackgroundIn a recent pilot report, we showed that Smac/DIABLO mRNA is expressed de novo in a subset of cervical cancer patients. We have now expanded this study and analyzed Smac/DIABLO expression in the primary lesions in 109 cervical cancer patients.MethodsWe used immunohistochemistry of formalin-fixed, paraffin-embedded tissue sections to analyze Smac/DIABLO expression in the 109 primary lesions. Seventy-eight samples corresponded to epidermoid cervical cancer and 31 to cervical adenocarcinoma. The median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…Thus, Smac downregulation may contribute to esophageal carcinogenesis. Reduced Smac expression has also been described in other types of cancer (11,38,(40)(41)(42). Importantly, our data revealed a significant association between Smac expression and chemotherapeutic response among the 31 ESCC patients who had undergone chemotherapy.…”
Section: Discussionsupporting
confidence: 62%
“…Thus, Smac downregulation may contribute to esophageal carcinogenesis. Reduced Smac expression has also been described in other types of cancer (11,38,(40)(41)(42). Importantly, our data revealed a significant association between Smac expression and chemotherapeutic response among the 31 ESCC patients who had undergone chemotherapy.…”
Section: Discussionsupporting
confidence: 62%
“…Thus, alteration of apoptosis is essential for cancer development and cancer cell death by radiation and chemotherapy is largely dependent upon apoptosis [16]. These data partially contradict those of others that smac/DIABLO expression does not correlate with stage, grade and prognosis [20,21].…”
Section: Discussioncontrasting
confidence: 56%
“…The members of the inhibitor of apoptosis (IAP) protein family are highly expressed in several classes of cancer. Interestingly, recent studies revealed that Smac is also differentially expressed in cervical tumors and in tumor cell lines [19,20]. These observations have prompted researchers to design Smac mimetic compounds that can be administered either alone or in combination with other chemotherapeutic agents to kill tumor cells.…”
Section: Discussionmentioning
confidence: 98%